2016
DOI: 10.1038/sc.2015.230
|View full text |Cite
|
Sign up to set email alerts
|

Modified Ashworth scale and spasm frequency score in spinal cord injury: reliability and correlation

Abstract: Study design: Intra-and inter-rater reliability study. Objectives: To assess intra-and inter-rater reliability of the Modified Ashworth Scale (MAS) and Spasm Frequency Score (SFS) in lower extremities in a population of spinal cord-injured persons, as well as correlations between the two scales. Setting: Clinic for Spinal Cord Injuries, Rigshospitalet, Hornbaek, Denmark. Methods: Thirty-one persons participated in the study and were tested four times in total with MAS and SFS by three experienced raters. Cohen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…This may explain why significant associations between physiological and self-report measures have not been reported here or previously. Since our self-report data matched published data (83% of our participants experienced muscle spasms, 75% reported increased muscle tone, high spasm frequency strongly associated with severe spasms; Figure 6 ; Kawamura et al, 1989 ; Little et al, 1989 ; Lechner et al, 2006 ; Baunsgaard et al, 2016 ), and many people with SCI describe their muscle spasms when asked about spasticity (Mahoney et al, 2007 ), our EMG results reinforce that individuals with SCI likely use spasms and/or tone to rate their spasticity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This may explain why significant associations between physiological and self-report measures have not been reported here or previously. Since our self-report data matched published data (83% of our participants experienced muscle spasms, 75% reported increased muscle tone, high spasm frequency strongly associated with severe spasms; Figure 6 ; Kawamura et al, 1989 ; Little et al, 1989 ; Lechner et al, 2006 ; Baunsgaard et al, 2016 ), and many people with SCI describe their muscle spasms when asked about spasticity (Mahoney et al, 2007 ), our EMG results reinforce that individuals with SCI likely use spasms and/or tone to rate their spasticity.…”
Section: Discussionsupporting
confidence: 85%
“…For example, individuals with spasticity had either pronounced or absent reciprocal inhibition but there was no difference in the degree of their spasticity when it was assessed clinically (tone, tendon reflexes, clonus; Crone et al, 1994 ). Self-reported spasm frequency scores correlated poorly with clinical assessment of perceived resistance against passive movement of the limb (i.e., tone using the modified Ashworth scale) or tendon reflexes (Priebe et al, 1996 ; Baunsgaard et al, 2016 ).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, its use is recommended by the National Institute of Neurological Disorders and Stroke (NINDS) Common Data Element (CDE) (36). In a previous study, we found the MAS to be reliable, assuming that the scale is considered as an ordinal scale (37). The sum-score of MAS used in the analysis is not validated, but a similar approach with a sum-score of spasticity has been used previously (25).…”
Section: Spasticitymentioning
confidence: 99%
“…The high frequency of painful spasms in patients was an important indication for the ITB pump implantation. The modified Ashworth spasticity scale and PSFS are well known scales for evaluating spasticity and spasm frequency in patients with other chronic neurologic disorders such as spinal cord injury and MS [30, 31]. …”
Section: Discussionmentioning
confidence: 99%